Avaliação da atividade antimicrobiana “in vitro” de resíduos de frutas exóticas frente a algumas bactérias contaminantes de alimentos - Santos, Tacila Rayane Jericó (2017)
The native and/or exotic tropical fruits of great agriculture-industrial potential, present a high potential for consumption. However, a great volume of residues containing several components bioativos has generated and discarded in the environment, causing serious environmental damages. In this context, this work had as objective the obtaining of extracts of different exotic fruits and evaluation of the potential antimicrobial of the same front the bacteria Bacillus cereus, Bacillus subtilis, Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Salmonella enteritidis, Serratia marcescens and Staphylococcus aureus. Initially they were obtained extracts of the residues of the fruits dekopon (Citrus reticulata 'Shiranui'), granadilla (Passiflora ligularis), kiwi (delicious Actinidia), bilberry (Vaccinium myrtillus), noni (Morinda citrifolia), sapodilla (Manilkara zapota), tamarillo (Solanum betaceum) and tamarind (Tamarindus indica) using the solvents distilled water, acetone, methanol and ethanol in concentrations from 40 to 80%, which were appraised as for the potential antimicrobial. Of these, the ones that introduced adult potential antimicrobial were the extracts of the junction peels and tamarind (ethanol 80%) seeds and the extracts of granadilla (acetone 80%) seed with values of concentration minimum inhibitory of 0,39 mg/mL. For these extracts, he/she took place experiments being varied the proportion solid:solvent, agitation and time of extraction, where it was evaluated the activity antimicrobial and composition of phenolic compounds and total flavonoids. The extract of the junction peel and tamarind seed with solvent ethanol 80% in the condition 5 (temperature: 36 ºC; reason solid:solvent, 15:10 and time: 50 min) and extract of granadilla seed with solvent acetone 80% in the condition 4 (temperature: 54ºC; reason solid:solvent 5:10 and time: 20 min), they were the ones that presented adult potential antimicrobial. On the other hand, the largest phenolics tenors (104,29 mg GAE.g.-1 and 31,21 mg GAE.g.-1 ) they were obtained in the conditions 12: (temperature: 45 ºC; reason solid:solvent: 6:10 and time: 35 min.) and 8: (temperature: 54 ºC; reason solid:solvent: 5:10 and time: 50 min) and total flavonoids (70,76 mg quercetina.g.-1 and 13,94 mg quercetina.g.-1 ) they were obtained in the conditions 4: (temperature: 54 ºC; reason solid:solvent: 5:10 and time: 20 min.) and 12: (temperature: 45 ºC; reason solid:solvent: 6:10 and time: 35 min.) for the extracts of granadilla seeds and junction of the peels and tamarind seeds, respectively. The extracts of the exotic fruits studied in this work and still no told in the literature demonstrated potential for they be used in future studies as natural antimicrobials of foods.